1995
DOI: 10.1200/jco.1995.13.3.588
|View full text |Cite
|
Sign up to set email alerts
|

BEAM chemotherapy and autologous bone marrow transplantation for patients with relapsed or refractory non-Hodgkin's lymphoma.

Abstract: Patients with chemosensitive disease benefit most from high-dose chemotherapy, and those who receive such therapy early after achieving a partial response to first-line therapy have a high rate of cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
218
3
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(242 citation statements)
references
References 11 publications
18
218
3
3
Order By: Relevance
“…11 Toxicities of BCNU-containing regimens, such as BEAM and BEAC, are concerning for a high incidence of interstitial pneumonitis. 12,13 Furthermore, results from the Bone Marrow Transplant Survivor Study have shown a significantly increased rate of non-relapse related mortality after autologous SCT for hematologic malignancies with BCNU-based regimens that was not observed with BU-or TBI-based regimens. 14 At risk: Few series using BU/CY as the conditioning regimen for autologous SCT in patients with relapsed NHL have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…11 Toxicities of BCNU-containing regimens, such as BEAM and BEAC, are concerning for a high incidence of interstitial pneumonitis. 12,13 Furthermore, results from the Bone Marrow Transplant Survivor Study have shown a significantly increased rate of non-relapse related mortality after autologous SCT for hematologic malignancies with BCNU-based regimens that was not observed with BU-or TBI-based regimens. 14 At risk: Few series using BU/CY as the conditioning regimen for autologous SCT in patients with relapsed NHL have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The overall survival at the time of transplantation was 93% for chemosensitive patients and 0% for chemoresistant patients (P<0.0001). Mills et al (18) reported a five-year progression-free survival of 49% for 55 chemosensitive patients with NHL, and 10% for 42 patients with chemoresistant lymphoma treated with HDT and ABMT. The main issue of this study is related to the important impact of HDCY on the diseases: 57.6% of patients achieved complete remission, 19 of 23 chemosensitive patients and 2 of 10 chemoresistant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-one patients underwent HDT. These patients received a 6-day period of chemotherapy according to the BEAM protocol (18). PBPC were re-infused on the day following HDT, nominally day 0 of the transplant procedure.…”
Section: High-dose Therapy and Autologous Bone Marrow Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…1) to 17% (ref. 4), depending on definition, but the risk of pneumonitis in patients with pre-existing lung disease is unknown. Our practice has been to omit BCNU when pre-transplant lung function tests showed a lung carbon monoxide transfer coefficient (KCO) of less than 50% or when there was pre-existing lung disease.…”
mentioning
confidence: 99%